Quantum Integrals for a Semi-Infinite q-Boson System with Boundary Interactions - van Diejen, J.F.; Emsiz, E. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
We provide explicit formulas for the quantum integrals of a semi-infinite q-boson system with boundary interactions. These operators and their commutativity are deduced from the Pieri formulas for a q→0 Hall-Littlewood type degeneration of the Macdonald-Koornwinder polynomials.